Hilazas de conocimiento (2020)
When taking a closer look to Bogota's city center we find ourselves surrounded by different types of architectural spaces that contain some sort of intellectuality and/or knowledge. Universities, schools, museums, theatres, historical monuments, administrative buildings, amongst many buildings with a knowledge content. Threads of Knowledge, seeks to generate a system that articulates these spaces both in the architectural and urban level, as a means to the consolidation of the city center through the richness of its intellectual programs and the history of the place itself.